What do educators need to know about the Torrance Tests of Creative Thinking: A comprehensive review - Alabbasi, Ahmed M. Abdulla; Paek, Sue Hyeon; Kim, Daehyun; Cramond, Bonnie (Frontiers in Psychology, 2022)
One of the most important questions that educators try to answer is how to prepare new generations of students for an unpredictable future. Students need to learn several skills, such as creativity, critical thinking, collaboration, and communication (the 4 Cs). Creativity, especially, is an essential skill in a complex and unforeseeable world/era, and an important step in any effort to enhance creativity is to identify students’ creative strengths and relative weaknesses. This review aims to offer school psychologists and other educators such as teachers, policymakers, and curriculum designers a comprehensive and practical guide to one of the most well-known creativity assessments—the Torrance Test of Creative Thinking (TTCT) that was developed by E. Paul Torrance in the 1960s. The paper discusses the history, components, training, psychometric properties, and uses of the TTCT. Contrary to the notion that the TTCT is only a measure of divergent thinking skills, the current article presents its other uses. It is the authors’ hope that teachers, school psychologists, and other educators will find the information reported in this article useful to better understand the TTCT and use it most effectively.